The Impact of Training & Development and Communication on Organizational Commitment on Bangladeshi Commercial Banks - Nishat Taslin Mohona; Umme kulsum; Jayashree Dey (Indonesian Journal Of Business And Economics, 2021)
Employees are the heart of an organization as they are the weapons that propel the organization towards its goal. However, to superintend and build them as competent, committed in the long run, it is challenging to experience supportive communication, fair bonding, and more clarity regarding the organization's goal and responsibility. Thus, this research intends to examine the impact of training development and communication on organizational commitment based on the private bank employees of Bangladesh, especially on the Chattogram division. A total of 153 responses were collected and analyzed through quantitative analysis and were tested in the statistical software SPSS (version 22). The findings show the significant relationship of training development and communication that are positively related to organizational commitment. The study suggests that commercial banks should introduce proper training development measurements that will clarify work activities, objectives, and a supportive communication system that can defend critical issues and relationships in the organization.